MIS 2021
DOI: 10.20517/2574-1225.2021.55
|View full text |Cite
|
Sign up to set email alerts
|

What role does hand-assistance have in minimally invasive pancreatic surgery?

Abstract: Surgery poses an important stress on the patient from both physical and psychological points of view per se. It has become clearer with time that, regardless of the type of surgical operation, a smaller surgical incision could reduce the operation-induced stress. With advancements in technology, great efforts have been made in trying to reduce this burden on the patient, leading to the development of minimally invasive surgery (MIS) [1,2] . MIS has gained increasing support since its introduction and has under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…HALDP could be used as an alternative option to convert from the total laparoscopic approach in cases where dissection is difficult, unclear anatomy or the risk of hemorrhage is high. It may also be used in cases of malignancy, where HALDP facilitates palpation of tumor and staging and can facilitate dissection for voluminous lesions [ 24 ]. Future research should consider separately analyzing patients who underwent hand-assisted distal pancreatectomy from those who had total laparoscopic distal pancreatectomy as they may confer different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…HALDP could be used as an alternative option to convert from the total laparoscopic approach in cases where dissection is difficult, unclear anatomy or the risk of hemorrhage is high. It may also be used in cases of malignancy, where HALDP facilitates palpation of tumor and staging and can facilitate dissection for voluminous lesions [ 24 ]. Future research should consider separately analyzing patients who underwent hand-assisted distal pancreatectomy from those who had total laparoscopic distal pancreatectomy as they may confer different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, this technology could also be preventing the stapling of tissue that is too thin, similarly decreasing the risk of intraoperative and postoperative complications. In a recent animal study, powered stapled anastomoses were found to have a higher burst pressure when compared to conventional stapling techniques [32,33,41] . On the surface, these advantages may appear to be minor benefits; nonetheless, our data clearly show that a potential benefit to HR liver resection in increasing the number of resections that can be done MI may exist, and this at least warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%